In-vitro antioxidant, anti-cancer, and anti-inflammatory activities of selected medicinal plants from western Nepal - Bishnu Prasad Pandey; Kapil Adhikari; Suman Prakash Pradhan; Hee Jeong Shin; Eun Kyeong Lee; Hye Jin Jung (SpringerOpen, 2020)
Abstract Background This study was focused on the measurement of anticancer properties of six medicinal plants from western Nepal in three cell lines; HeLa, Hep3B, and HCT116, and anti-inflammatory properties in RAW 264.7 cell line through NO, PGE2, and TNF-α production. In addition, the phytochemical screening, total phenolic, flavonoid content, and antioxidant properties were evaluated. Results The qualitative phytochemical analysis revealed the presence of different secondary metabolite and range of total phenolic and total flavonoid content. The highest antioxidant activities were observed in Bergenia pacumbis against both DPPH (IC50 = 25.97 ± 0.19 μg/mL) and ABTS (IC50 = 14.49 ± 0.40 μg/mL). Furthermore, the highest antiproliferative effect against cervical, liver, and colon cancer cell lines were observed in Melia azedarach as IC50 values of 10.50, 5.30, and 1.57 μg/mL respectively, while the strongest anti-metastatic potential on liver cancer cell line was found in Pleurospermum benthamii. In addition, P. benthamii showed the most potent anti-inflammatory effect in RAW264.7 murine macrophage cells. Conclusion This study provided the evidence for M. azedarach and P. benthamii to have great anticancer potential and finding builds the enough scientific backgrounds in future to isolate and purify the bioactive compounds for further applications.